Analysis of the Political System in Indonesia - Asep Wianto (Jurnal Mantik, 2022)
This article was written with the aim of providing an analysis of the political system that occurs in Indonesia, as it is known that the political system is often considered as an allocation of values ??that develops in the midst of society and every citizen appreciates it as a culture, value, norm that has existed for a long time. time. Basically, post-reform, the political system in Indonesia is getting better, where the role of the people is more real in terms of repositioning the political system, starting from the election of members of the DPR/DPRD, the election of members of the DPD, to the direct election of regional heads. The research method used by the researcher includes descriptive analysis, based on a qualitative approach, the results of this study explain that, currently the power system in Indonesia is divided into four parts with 7 main institutions as power holders in their respective duties and functions. has been mandated by law, namely the executive, legislative and judicial. Basically democracy is closely related to democratization, where this term is often interpreted as a political process carried out by the government together with the community to create a democratic political life. The Indonesian political system itself is strongly influenced by the environment around it, besides that the Indonesian political system can also be easily influenced by political culture and is highly dependent on the existence of its political parties. As a system, political culture should also have an orientation that aims to seek welfare for all its citizens. And explicitly the existence of political parties in Indonesia can be a bridge between civil society and people's representatives, especially in conveying their state aspirations.